Survivorship of 157 arthroscopic meniscal allograft transplants using bone fixation at a mean of 7 years and prognostic factors analysis - Husen, Martin; Poudel, Keshav; Wang, Allen; Saul, Dominik; Stuart, Michael J.; Levy, Bruce A.; Saris, Daniël B.F.; Krych, Aaron J. (The American journal of sports medicine, 2024)
Background: Meniscal allograft transplantation (MAT) is an accepted and effective treatment option in the context of unsalvageable menisci, particularly in young and active patients. It has been shown to reduce pain and improve knee function in previously symptomatic patients. However, there is still limited knowledge about the long-term survival rates of allografts, the durability of clinical results, and the influence of patient-specific parameters, such as leg alignment, tibial slope, and preoperative International Cartilage Regeneration & Joint Preservation Society (ICRS) grade. - Purpose: To determine (1) the long-term clinical success rate after MAT with bony fixation in a large, single-center cohort of consecutive patients, and (2) if patient-specific and procedural variables influence the clinical, anatomic, and subjective outcomes and risk of failure. - Study Design: Case-control study; Level of evidence, 3. - Methods: Data on 185 consecutive knees undergoing MAT in a single institution were prospectively collected and screened for inclusion in this study. The minimum follow-up time was 2 years. Radiographic variables (ICRS grade and Kellgren-Lawrence grade) were assessed preoperatively and at follow-up. Subjective patient-reported outcome measures (PROMs) (Lysholm score, Knee injury and Osteoarthritis Outcome Score [KOOS] including subscores, International Knee Documentation Committee [IKDC] score, and visual analog scale [VAS] score) were collected preoperatively and at follow-up. Clinical failure was defined as revision surgery due to graft failure or conversion to total knee arthroplasty. Anatomic failure was considered a tear covering >20% of the allograft, any peripheral tear, and unstable peripheral fixation leading to dislocation of the graft. Subjective failure was defined as Lysholm score ≤65. Preoperative tibial slope and leg alignment were assessed. Survival analyses were performed using the Kaplan-Meier estimate. Univariate and multivariate analyses were performed to determine risk factors for clinical and anatomic failure. - Results: A total of 157 knees met inclusion criteria. After a mean follow-up time of 7 ± 3.5 years, 127 (80.9%) knees were free of clinical, anatomic, and subjective failure. Fourteen (8.9%) knees experienced clinical failure, 26 (16.6%) knees were identified as having experienced anatomic failure, and 13 (8.3%) patients experienced subjective failure with a reported Lysholm score of ≤65 at a mean follow-up of 7 years. Concurrent osteochondral allograft transplantation was identified as a predictor of both clinical (hazard ratio [HR], 4.55; 95% CI, 1.46-14.17; P = .009) and anatomic (HR, 3.05; 95% CI, 1.34-6.92; P = .008) failure. Cartilage damage of ICRS grade 3 or 4 of the index compartment conveyed an increased risk for clinical (HR, 3.41; 95% CI, 1.05-11.01; P = .04) and anatomic (HR, 3.04; 95% CI, 1.31-7.11; P = .01) failure. High-grade cartilage damage preoperatively (HR, 10.67; 95% CI, 1.037-109.768; P = .046), patient age >25 years (HR, 5.44; 95% CI, 0.120-246.070; P = .384), and a body mass index >30 (HR, 2.24; 95% CI, 0.748-6.705; P = .149) were associated with subjective failure. PROMs including KOOS and IKDC were significantly improved at final follow-up compared with preoperative scores across all measurements (P < .005). - Conclusion: MAT showed good to excellent clinical results at a mean follow-up of 7 years. Low ICRS lesion grade was associated with a higher clinical and anatomic survival rate. Patients with concurrent OCA transplantation are at a higher risk of clinical and anatomic failure, but still report significantly improved PROMs. These results suggest that MAT has a lasting beneficial effect both in isolation and in complex cases with ≥1 concurrent procedures.
Gesehen am 06.08.2024